2022
DOI: 10.3390/biomedicines10061263
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Improves Spatial Learning and Memory Impairment in Rats with Liver Damage-Associated Neuroinflammation

Abstract: Patients with non-alcoholic fatty liver disease (NAFLD) may show mild cognitive impairment. Neuroinflammation in the hippocampus mediates cognitive impairment in rat models of minimal hepatic encephalopathy (MHE). Treatment with rifaximin reverses cognitive impairment in a large proportion of cirrhotic patients with MHE. However, the underlying mechanisms remain unclear. The aims of this work were to assess if rats with mild liver damage, as a model of NAFLD, show neuroinflammation in the hippocampus and impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…Visuospatial memory and learning impairments are a known feature of experimental rodent [68], as well as human, MASH [5]. In our study, we observed a long-term decrease in spatial memory, as shown in the SATM test, but no change in object-recognition memory.…”
Section: Discussionsupporting
confidence: 62%
“…Visuospatial memory and learning impairments are a known feature of experimental rodent [68], as well as human, MASH [5]. In our study, we observed a long-term decrease in spatial memory, as shown in the SATM test, but no change in object-recognition memory.…”
Section: Discussionsupporting
confidence: 62%
“…This finding is supported by other studies of HE models. In the type C HE model induced by carbon tetrachloride (CCl4), microglia activation and increased pro-inflammatory cytokines in the CA1 region of the hippocampus were noted, along with spatial learning and memory impairments [73]. More importantly, chronic hyperammonemia was shown to induce neuroinflammation in the hippocampus [4].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in rat models of MHE with mild liver damage similar to non-alcoholic fatty liver disease (NAFLD) [ 107 ] showed hippocampal neuroinflammation with consequent spatial learning and memory impairment. Increase in CCL2 levels in the hippocampus could be an early event that promotes microglia activation and monocytes infiltration, with their conversion in macrophages.…”
Section: Intestinal Microbiota Modulation As Treatment Strategy and E...mentioning
confidence: 99%